Foundations and Contemporary Relevance of Salafi Islamic Education in Indonesia: Principles, Curriculum, and Moral Development - Ilhamsyah, Rizal; Ramli, Mohammad (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2024)
This study analyzes the foundational principles, curriculum structure, and contemporary contributions of Salafi Islamic educational institutions in Indonesia, focusing on their adherence to the manhaj salaf methodology. Employing a qualitative conceptual analysis through a structured literature review of 34 scholarly sources from 2010 to 2024, it explores the theological underpinnings, pedagogical approaches, and institutional responses to modernity. Salafi education prioritizes the purification of Islamic teachings, emphasizing tawḥīd, memorization of the Qur’an and ḥadīth, and traditional instructional methods such as halaqah and talaqqī. Secular knowledge integration remains minimal and strategic, preserving doctrinal orthodoxy. The institutions contribute significantly to moral and character development by fostering ethical discipline grounded in prophetic teachings. While cautious, selective adaptations to globalization and technological advances are evident, ensuring educational relevance without compromising core values. Limitations include reliance on textual analysis without empirical fieldwork, prompting recommendations for future research on practical implementations and comparative pedagogical models. The study underscores Salafi education’s vital role in maintaining Islamic orthodoxy and moral integrity within Indonesia’s pluralistic context, advocating for ongoing epistemological dialogue to balance doctrinal fidelity and educational openness.